Analisis Biaya dan Pendapatan Budidaya Jamur Tiram Putih di UMKM Jamur Betuah Kota Pekanbaru - Ahmad Guswandi; Dini Amalia Putri (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
Indonesia’s agricultural sector plays a vital role in food security, increasing community income, and improving nutrition through food diversification. One of its main subsectors is horticulture, with white oyster mushrooms (Pleurotus ostreatus) as a highâ€“economicâ€“value commodity whose demand continues to rise. This study analyzes the costs and income of white oyster mushroom cultivation at UMKM Jamur Betuah in Pekanbaru through field observation, interviews, and quantitative descriptive analysis. From 1,500 baglogs, a total of 950 kg of mushrooms are produced per cycle, with total production costs of IDR 57,133,600 and revenue of IDR 375,000,000, resulting in a net income of IDR 317,866,400. The Break Even Point (BEP) analysis of 0.15 indicates that the break-even point can be reached at a low production level. These findings confirm that white oyster mushroom cultivation at UMKM Jamur Betuah has strong economic prospects and is feasible to develop as a sustainable agribusiness.